2018
DOI: 10.3390/sym10020042
|View full text |Cite
|
Sign up to set email alerts
|

Diagonally Implicit Multistep Block Method of Order Four for Solving Fuzzy Differential Equations Using Seikkala Derivatives

Abstract: Abstract:In this paper, the solution of fuzzy differential equations is approximated numerically using diagonally implicit multistep block method of order four. The multistep block method is well known as an efficient and accurate method for solving ordinary differential equations, hence in this paper the method will be used to solve the fuzzy initial value problems where the initial value is a symmetric triangular fuzzy interval. The triangular fuzzy number is not necessarily symmetric, however by imposing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Consider the scalar test equation y = λy. Substitute hλ =h into (11) and rewrite it in the matrix form to get…”
Section: Zero Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the scalar test equation y = λy. Substitute hλ =h into (11) and rewrite it in the matrix form to get…”
Section: Zero Stabilitymentioning
confidence: 99%
“…Because of the high cost of evaluating the stages in a fully implicit method, [9] reported that many researchers have opted to reduce it to a diagonally implicit method. Prior works along this line were discussed by [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The series solution is computed for the upper and lower approximation in each subdomain separately. The initial values at the point t = 0.9 are the terminal values of the previous series, which is y1 = 2.1518γ + 2.6452, y1 = 6.9488 − 2.1518γ y2 = 6.9108γ + 19.1886, y2 = 33.0103 − 6.91086γ (26) A similar method is followed for other points, and the results are represented in Table 6. These results show that the solution has no switching point, and the system has D 2 1,1 differentiability in the domain.…”
Section: Solutionmentioning
confidence: 99%
“…Fuzzy differential equations are solved using many methods, such as differential or fuzzy inclusion [10][11][12], the extension principle and characterization theorem [13][14][15], and artificial neural networks [16]. Numerical methods such as the differential transformation method [17,18], extension of numerical solution methods for ordinary differential equations (ODEs) [19][20][21][22][23][24], interactive derivatives [25], multistep methods [26], and Runge-Kutta (RK) methods [27] are also applied to solving these equations. The metric properties of fuzzy functions are studied in [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This inexactitude extends to the requirement of fuzzy differential equations (FDEs) to surmount the problem. This aspect of fuzzy differential equations takes place in numerous studies like scientific discipline, economic science, psychological science, defense mechanism, human ecology and applied sciences [17], [23], [36] and [39].…”
Section: Introductionmentioning
confidence: 99%